Analisis Biaya Standar Sebagai Alat Pengedalian Biaya Produksi Pada CV. Pia Manalagi Probolinggo - Anita Rahman; Mohammad Iskak Elly; R Hery Koeshardjono (JUMAD : Journal Management, Accounting, & Digital Business, 2023)
This study aims to determine the standard cost analysis as a means of controlling production cost at CV. Pia Manalagi Probolinggo. The research method used in desceiptive quantitative. The source of data in this study is secondary data using interview and documentation techniques. Analysis of the data used is the analysis of the difference (variance). The results of the study show that the difference in production costs that occur in CV. Pia Manalagi Probolinggo, namely the difference in raw material costs in 2021 and 2022 is unfavourable difference, the difference in direct labor costs in 2021 and 2022 is no difference, and the difference in factory overhead cost in 2021 is unfavourable difference and in 2022 experienced a frofitable difference.